BETWEEN ECO-EDUCATION AND CRITICAL THINKING: THE APPLICATION OF EMANCIPATORY LEARNING ON GAINING THE AWARENESS OF ENVIRONMENTAL PROBLEMS IN BALI - Desi Wulandari, Ni Putu (International Conference on Cultural Studies, 2018)
This article is aimed at explicating the environmental problems in Bali and explaining that emancipatory learning is an idealism of learning applied to gain critical thinking of Balinese young generation on the importance of environment sustainability. This is a non reasearch article or a review article in a form of descriptive style regarding critical education and cultural study as its basic idealism. This review article generaly summarizes the existing literatures on a topic in an attempt to explain the current state of understanding on the topic. This article was written in form of narrative style of article writing. There are several matters to be reviewed in this article from various literatures and writers; environmental sustainability problems in Bali, the education system in Indonesia as it is applied in Bali, Balinese cultural contribution on environmental sustainability, the concept of hegemony, critical education and emancipatory learning, eco education and thus, the correlation between all those matters. Especially on emancipatory learning explanation, this article lists several strategies in combining emancipatory learning and eco education. There are several names of expert to be appeared in this article such as Gramsci, Giroux and Freire.